2020
DOI: 10.3390/rs12233904
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Surface Concentrations of Black Carbon from Long-Term Measurements at Aeronet Sites over Korea

Abstract: We estimated fine-mode black carbon (BC) concentrations at the surface using AERONET data from five AERONET sites in Korea, representing urban, rural, and background. We first obtained the columnar BC concentrations by separating the refractive index (RI) for fine-mode aerosols from AERONET data and minimizing the difference between separated RIs and calculated RIs using a mixing rule that can represent a real aerosol mixture (Maxwell Garnett for water-insoluble components and volume average for water-soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The correlation between the concentration of eBC and the values of atmospheric pressure, relative humidity, and precipitation was weak or statistically insignificant (Table 3). Lack of a clear relationship between precipitation and relative humidity and eBC concentration may result from the fact that freshly emitted BC particles have a hydrophobic character; thus, they are excluded from liquid droplets or are associated with an insoluble phase [47,70,71]. Compared to the above-mentioned meteorological parameters, wind speed is more effective in reducing eBC concentration at the sampling site.…”
Section: Identification Of Factors Influencing the Concentration Of Ebcmentioning
confidence: 99%
“…The correlation between the concentration of eBC and the values of atmospheric pressure, relative humidity, and precipitation was weak or statistically insignificant (Table 3). Lack of a clear relationship between precipitation and relative humidity and eBC concentration may result from the fact that freshly emitted BC particles have a hydrophobic character; thus, they are excluded from liquid droplets or are associated with an insoluble phase [47,70,71]. Compared to the above-mentioned meteorological parameters, wind speed is more effective in reducing eBC concentration at the sampling site.…”
Section: Identification Of Factors Influencing the Concentration Of Ebcmentioning
confidence: 99%
“…These estimates indicate, in particular, that the IRI of OA originating from biomass burning is strongly variable, ranging from virtually zero to almost 0.04 (at the 550 nm wavelength). Reported estimates of the MAE of OA (e.g., Alexander et al, 2008;Favez et al, 2009;Yang et al, 2009;Cheng et al, 2011;Chung et al, 2012a;Olson et al, 2015) have been derived, albeit in a much simpler way, mostly from in situ observations of the absorption coefficients and OA (or organic carbon, OC) mass concentration and are also very diverse, differing by orders of magnitude. Typically, such estimates involve strong assumptions about the spectral dependence of the BC absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The BC and BC + BrC fractions displayed different seasonal characteristics. In a previous study, the BC mass density at Yonsei_University was highest in spring and winter during 2011-2018 (Choi et al, 2020), which could explain why our study identified the highest BC + BrC fraction in spring. Compared with the characteristics of BC + BrC, the characteristics of BC were more similar to the distribution tendency of NA.…”
Section: Seasonal Characteristicsmentioning
confidence: 42%